CD4+ T cells inhibit the neu-specific CD8+ T-cell exhaustion during the priming phase of immune responses against breast cancer - Kmieciak, Maciej (2010)
Studies conducted in animal model of infectious diseases or H-Y antigen model suggest a crucial role for CD4+ T cells in providing help for CD8+ T-cell memory responses. This concept suggests that inclusion of T helper epitopes in vaccine formulation will result in improved CD8+ T-cell responses. Although this concept has been applied to cancer vaccine design, the role of CD4+ T cells in the memory differentiation of CD8+ T cells and retention of their anti-tumor function have never been tested in breast cancer model. Using the FVB mouse model of neu-positive breast carcinoma we report for the first time that helpless T cells showed cytostatic or tumor inhibitory effects during primary tumor challenge whereas, helped T cells showed cytotoxic effects and resulted in complete tumor rejection. Such differential effects, in vivo, were associated with higher frequency of CD8+PD-L1+ and CD8+PD-1+ T cells in animals harboring helpless T cells as well as higher titer of IL-2 in the sera of animals harboring helped T cells. However, depletion of CD4+ T cells did not alter the ability of neu-specific CD8+ T cells to differentiate into memory cells and to retain their effector function against the tumor during recall challenge. These results suggest the inhibitory role of CD4+ T cells on CD8+ T-cell exhaustion without substantial effects on the differentiation of memory T cells during priming phase of the immune responses against breast cancer.